(untitled) (BIRDEM Medical Journal, 2012)
Acute tubular necrosis (ATN) is a medical condition involving damage of the tubular cells of the nephron following a toxic or ischaemic injury. If the cause of ATN is removed then recovery is likely. Calcineurin inhibitors (ciclosporin & tacrolimus) are used as immunosuppressive agents in renal transplant recipient. But either of these two drugs can cause acute nephrotoxicity. A 62 years old known diabetic, hypertensive & ESRD patient after undergoing living related donor renal transplantation started passing significant amount of urine, but 12 hrs after transplantation the amount of urine output started to decrease and the patient became anuric after 17hrs of transplantation. Immediately the patient was evaluated thoroughly and calcineurin inhibitor (tacrolimus) was witheld. The patient again started passing urine from 4th POD. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12365 Birdem Med J 2012; 2(1) 63-65